ANALISIS BETON SERAT DENGAN KAWAT BENDRAT DAN SUBSTITUSI AGREGAT KASAR DENGAN LIMBAH PLASTIK - Deddy Kurniawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Concrete is a composition of materials consisting mainly of binding media in which particles or aggregate pigments are embedded. Normal concrete weighs between 1900 kg/m³ to 2400 kg/m³, for the development of concrete technology in this study with the aim of increasing the datility associated with the ability of the material to absorb energy, resistance to shock loads, fatique life, shrinkage, abrasion, fragmentation and spalling as well as the ability to withstand pull and bending moments but have a lighter concrete weight. The effect of normal concrete mixture with rough aggregate substitution with plastic waste recycling on normal concrete with strong press results on concrete life of 14 and 28 days consecutively press strength of 18.98% and 14.21%, and directly proportional to crack time of 11.47% and 16.97%. The resulting crack pattern is dominated by the destruction of cones and halves. The effect of normal concrete mixture with the addition of bendrat wire to normal concrete with strong press results on concrete life of 14 and 28 days respectively press strength 34.31% and 20.47%, and directly proportional to crack time of 20.67% and 4.04%. The resulting crack pattern is predominantly a form of cone destruction and shear. The effect of normal concrete mixture with rough aggregate substitution with recycling of plastic waste and the addition of bendrat wire to normal concrete with strong press results on concrete life of 14 and 28 days respectively press strength of 6.57% and -5.30%, and not directly proportional to crack time of -9.96% and -1.72%. The resulting crack pattern is dominated by a form of shear destruction.